Serum lipoproteins in day and shift workers: a prospective study. Issue 2 (February 1990) - Knutson, A; Andersson, H; Berglund, U
Abstract : This study was designed to assess changes in diet and serum lipoproteins in shift workers. Twelve shift workers and 13 day workers were examined before employment and after six months at work. Total cholesterol and serum triglycerides did not change significantly. In both groups a decrease in systolic blood pressure was observed. The ratio between apoB and apoA-1 lipoproteins increased by 18% in shift workers compared with 5% in day workers. The change in the ratio between apoB and apoA-1 lipoproteins showed a significant inverse correlation with the change in intake of dietary fibres.